Correlation of creative thinking abilities and student learning outcomes through the application of ethnoscience-based project-based learning methods - Wally , Pramita; Marwah, Andi Sitti; Kurniawati , Ivatul Laily (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
Educators in the 21st century are challenged to be able to design and determine learning methods according to the concept of local wisdom that will be taught to improve creative thinking skills and learning outcomes. This study aims to determine the relationship between the level of creative thinking and student learning outcomes through the application of ethnoscience-based project-based learning (PjBL). This type of research is a quantitative study using a pre-experimental design with the type of one-group design. The sample in this study was the 3rd-semester biology class of the Biology Education Study Program, Muhammadiyah University of Maluku, totaling 20 students. The independent variable in this study is the ethnoscience-based project-based learning model. In contrast, the dependent variable is student learning outcomes and students' creative thinking abilities in herbal botany courses. The types of research instruments used were questionnaires and essay tests, comprising 15 items. The data found were then analyzed using the product-moment correlation test to determine the relationship with SPSS version 23 at a significance level of 0,05. The results of this study indicate that there is a positive relationship between the level of creative thinking of students and learning outcomes as shown by the results of the regression test of 5.6%. so it is suggested to lecturers or teachers to further improve creativity and student learning outcomes so that project-based learning methods based on ethnoscience can be used.